The evaluation of the expression, if m = − 4 , n = 1 , p = 2 , q = − 6 , r = 5 , and t = − 2 | 16 + 4 ( 3 q + p ) is 46.
<h3>How can the expression be simplified?</h3>
the given expression is t = − 2 | 16 + 4 ( 3 q + p )
Then since we are given m = − 4 , n = 1 , p = 2 , q = − 6 , r = 5
Then, we can substitute all the given values of the terms into the given expression as :
t = − 2 | 16 + 4 ( 3 q + p )
t= -2 I 16+4(-18+2)
t= -2 I 16+4(-16)
t= -2 I 16 -64
t= -2 I -48
t =46
Read more about expression at:
brainly.com/question/723406
#SPJ1
Angles that equal 180 degrees
Answer:
PR=22
Step-by-step explanation:
3x+6x+4=14x-6
9x+4=14x-6
10=5x
x=2
Plug in
3(2)
6
6(2)+4
12+4
16
16+6
22
So the bottom should equal 22
14(2)-6
28-6
22
Hope this helps
Brainliest would be appreciated
X^2 + 16x + 64
= (x + 8)^2
length of the side = 25+8 = 33 feet
<span>Because he couldn't find a date</span>